GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 13 Oct 2019, 23:46 GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  If 3^x - 3^(x-1) = 162, then x(x - 1) =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

Hide Tags

Intern  Joined: 09 Jan 2009
Posts: 6
If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

1
10 00:00

Difficulty:   25% (medium)

Question Stats: 75% (01:41) correct 25% (01:59) wrong based on 272 sessions

HideShow timer Statistics

If $$3^x - 3^{(x-1)} = 162$$, then x(x - 1) =

A. 12
B. 16
C. 20
D. 30
E. 81

Attachment: Picture 8.png [ 9.86 KiB | Viewed 4567 times ]

Originally posted by troop2118 on 14 Jan 2009, 03:54.
Last edited by Bunuel on 11 Oct 2019, 06:08, edited 3 times in total.
Renamed the topic, edited the question, added the OA and moved to PS forum.
GMAT Tutor G
Joined: 24 Jun 2008
Posts: 1810
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

3
7
Just as you'd factor out the term with the smaller power if you saw something like $$x^8 - x^7$$ (you'd factor out $$x^7$$) you can factor out the term with the smaller power here:

\begin{align*} 3^x - 3^{x-1} &= 162 \\ 3^{x-1}(3 - 1) &= 162 \\ 3^{x-1} &= 81 \\ x - 1 &= 4 \end{align*}

So x = 5, and x*(x-1) = 20.
_________________
GMAT Tutor in Toronto

If you are looking for online GMAT math tutoring, or if you are interested in buying my advanced Quant books and problem sets, please contact me at ianstewartgmat at gmail.com
General Discussion
Senior Manager  Joined: 28 Jun 2009
Posts: 354
Location: United States (MA)
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

1
For me, fastest method was plugging in the answer choices.

From the answer choices, only 12, 20 and 30 satisfy x(x-1).

Among these only 20 i.e. x = 5 satisfies : 3^x - 3^(x-1) = 162

Hence answer is C.
Manager  Joined: 09 Nov 2011
Posts: 108
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

1
3^x - 3^x-1=162
3^x[1-1/3]=162
3^x[2/3]=162
3^x=81*3
=>x=5
x(x-1) =5*4 = 20
Hence C
_________________
Time to play the game...
EMPOWERgmat Instructor V
Status: GMAT Assassin/Co-Founder
Affiliations: EMPOWERgmat
Joined: 19 Dec 2014
Posts: 15240
Location: United States (CA)
GMAT 1: 800 Q51 V49 GRE 1: Q170 V170 Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

Hi All,

If you're not an expert at tougher exponent rule questions such as this, you can sometimes get to the answer with a bit of "brute force", even without knowing the exact exponent rules involved in the prompt. Here's how:

This question involves 3 raised to different "powers"; you can calculate them rather easily...

3^1 = 3
3^2 = 9
3^3 = 27
3^4 = 81
3^5 = 243

3^X and 3^(X-1) are consecutive powers of 3.
We're told that 3^X - 3^(X-1) = 162, so we just need to find 2 consecutive multiples of 3 that differ by 162.

Notice how...
3^5 - 3^4 =
243 - 81 =
162

This is EXACTLY what we're looking for.

X = 5
(X-1) = 4

So....(X)(X-1) = (5)(4) = 20

GMAT assassins aren't born, they're made,
Rich

--== Message from the GMAT Club Team ==--

THERE IS LIKELY A BETTER DISCUSSION OF THIS EXACT QUESTION.
This discussion does not meet community quality standards. It has been retired.

If you would like to discuss this question please re-post it in the respective forum. Thank you!

To review the GMAT Club's Forums Posting Guidelines, please follow these links: Quantitative | Verbal Please note - we may remove posts that do not follow our posting guidelines. Thank you.

_________________
Director  V
Joined: 04 Dec 2015
Posts: 745
Location: India
Concentration: Technology, Strategy
WE: Information Technology (Consulting)
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

3
1
troop2118 wrote:
If 3^x - 3^(x-1) = 162, then x(x - 1) =

A. 12
B. 16
C. 20
D. 30
E. 81

Attachment:
Picture 8.png

$$3^x - 3^{(x-1)} = 162$$

$$3^x - (3^x*3^{-1}) = 162$$

$$3^x - (\frac{3^x}{3^{1}}) = 3^4*2$$

$$\frac{3*3^x - 3^x}{3} = 3^4*2$$

$$\frac{3^x(3 - 1)}{3} = 3^4*2$$

$$3^x(3 - 1) = 3^4*2*3$$

$$3^x(2) = 3^5*2$$

$$3^x = 3^5$$

$$x = 5$$

$$x (x-1) = 5(5-1) = 5*4 = 20$$

_________________
Please Press "+1 Kudos" to appreciate. Target Test Prep Representative D
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 8040
Location: United States (CA)
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

troop2118 wrote:
If 3^x - 3^(x-1) = 162, then x(x - 1) =

A. 12
B. 16
C. 20
D. 30
E. 81

We can simplify the left side of the equation and then factor 162 as 3^4 * 2^1. Then we have:

3^x - 3^x * 3^-1 = 3^4 * 2^1

3^x(1 - 3^-1) = 3^4 * 2^1

On the left side, note that the expression (1 - 3^-1) = 1 - (⅓) = ⅔. We now have:

3^x(2/3) = 3^4 * 2^1

3^x = (3^4 * 2)(3/2)

3^x = 3^4 *3

3^x = 3^5

x = 5

So x(x-1) = 5(4) = 20.

Alternate Solution:

Note that 3^x = 3 * 3^(x - 1). Then:

3^x - 3^(x - 1) = 3 * 3^(x - 1) - 3^(x - 1)

Let’s factor the common 3^(x - 1):

3 * 3^(x - 1) - 3^(x - 1) = 3^(x - 1)(3 - 1) = 3^(x - 1)(2) = 162

3^(x - 1) = 81 = 3^4

x - 1 = 4

x = 5

Then, x(x - 1) = 20.

_________________

Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

If you find one of my posts helpful, please take a moment to click on the "Kudos" button.

CEO  V
Joined: 12 Sep 2015
Posts: 3990
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

Top Contributor
troop2118 wrote:
If 3^x - 3^(x-1) = 162, then x(x - 1) =

A. 12
B. 16
C. 20
D. 30
E. 81

Attachment:
Picture 8.png

Given: 3^x - 3^(x-1) = 162
Factor to get: [3^(x-1)][3^1 - 1] = 162
Simplify to get: [3^(x-1)] = 162
Divide both sides by 2 to get: 3^(x-1) = 81
Rewrite the right side as 3^(x-1) = 3^4
So, x - 1 = 4
This means x = 5

We get x(x - 1) = (5)(5 - 1) = (5)(4) = 20

RELATED VIDEO FROM OUR COURSE

_________________
EMPOWERgmat Instructor V
Status: GMAT Assassin/Co-Founder
Affiliations: EMPOWERgmat
Joined: 19 Dec 2014
Posts: 15240
Location: United States (CA)
GMAT 1: 800 Q51 V49 GRE 1: Q170 V170 Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

Hi All,

We're told that 3^(X) - 3^(X-1) = 162. We're asked for the value of then (X)(X-1). This question can be solved rather easily with a bit of 'brute force' arithmetic.

Since we're dealing with 'powers of 3', let's map out the first several values:
3^1 = 3
3^2 = 9
3^3 = 27
3^4 = 81
3^5 = 243

We're subtracting two consecutive powers of 3 and ending up with 162. Looking at the list so far, we have an obvious 'pair' of values that fits what we're looking for:

3^5 and 3^4
243 - 81 = 162

Thus, X = 5 and the answer to the question is (5)(5-1) = 20

GMAT assassins aren't born, they're made,
Rich
_________________
GMATH Teacher P
Status: GMATH founder
Joined: 12 Oct 2010
Posts: 935
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

troop2118 wrote:
If 3^x - 3^(x-1) = 162, then x(x - 1) =

A. 12
B. 16
C. 20
D. 30
E. 81

$$? = x\left( {x - 1} \right)$$

$$\left. \begin{gathered} {3^x} - {3^{x - 1}} = {3^{x - 1}}\left( {3 - 1} \right)\,\,\, \hfill \\ 162 = 2 \cdot 81 = 2 \cdot {3^4} \hfill \\ \end{gathered} \right\}\,\,\,\,\,\,\,\mathop \Rightarrow \limits^{{\text{stem}}} \,\,\,\,\,\,\,{3^{x - 1}} = {3^4}\,\,\,\,\,\,\,\mathop \Rightarrow \limits^{{\text{3}}\,\, \notin \,\,\left\{ {0,1, - 1} \right\}} \,\,\,\,\,\,\,x - 1 = 4\,\,\,\,\,\,\,\, \Rightarrow \,\,\,\,\,\,\,? = 20$$

This solution follows the notations and rationale taught in the GMATH method.

Regards,
Fabio.
_________________
Fabio Skilnik :: GMATH method creator (Math for the GMAT)
Our high-level "quant" preparation starts here: https://gmath.net
Senior Manager  S
Joined: 12 Sep 2017
Posts: 301
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

ScottTargetTestPrep wrote:
troop2118 wrote:
If 3^x - 3^(x-1) = 162, then x(x - 1) =

A. 12
B. 16
C. 20
D. 30
E. 81

We can simplify the left side of the equation and then factor 162 as 3^4 * 2^1. Then we have:

3^x - 3^x * 3^-1 = 3^4 * 2^1

3^x(1 - 3^-1) = 3^4 * 2^1

On the left side, note that the expression (1 - 3^-1) = 1 - (⅓) = ⅔. We now have:

3^x(2/3) = 3^4 * 2^1

3^x = (3^4 * 2)(3/2)

3^x = 3^4 *3

3^x = 3^5

x = 5

So x(x-1) = 5(4) = 20.

Alternate Solution:

Note that 3^x = 3 * 3^(x - 1). Then:

3^x - 3^(x - 1) = 3 * 3^(x - 1) - 3^(x - 1)

Let’s factor the common 3^(x - 1):

3 * 3^(x - 1) - 3^(x - 1) = 3^(x - 1)(3 - 1) = 3^(x - 1)(2) = 162

3^(x - 1) = 81 = 3^4

x - 1 = 4

x = 5

Then, x(x - 1) = 20.

Hello ScottTargetTestPrep !

Would you be so kind and explain to me how did you get to the following?

Note that 3^x = 3 * 3^(x - 1). Then:

3^x - 3^(x - 1) = 3 * 3^(x - 1) - 3^(x - 1)

Kind regards!
Target Test Prep Representative D
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 8040
Location: United States (CA)
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

So here are some more details:

3^x = 3^[x - 1 + 1] = 3^[(x - 1) + 1] = [3^(x - 1)]*[3^1] = 3*3^(x - 1)

However, that's a long and complicated way of putting things. In reality, you would just observe that given any power, you can always decrease the exponent by one and multiply with the base to get an equivalent expression. For instance, if you have 2^5 (which is 2 multiplied by itself five times), that is equal to [2^4]*2 (which is 2 multiplied by itself four times, and then multiplied by 2 once more).

In the next line, all we did was to replace 3^x by the equivalent expression of 3*3^(x - 1) which we obtained as explained above.

Posted from my mobile device
_________________

Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

If you find one of my posts helpful, please take a moment to click on the "Kudos" button.

Non-Human User Joined: 09 Sep 2013
Posts: 13080
Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =  [#permalink]

Show Tags

Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________ Re: If 3^x - 3^(x-1) = 162, then x(x - 1) =   [#permalink] 11 Oct 2019, 06:04
Display posts from previous: Sort by

If 3^x - 3^(x-1) = 162, then x(x - 1) =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne  